2021
DOI: 10.1055/s-0041-1740130
|View full text |Cite
|
Sign up to set email alerts
|

Free Medial Femoral Condyle Flap for Reconstruction of Scaphoid Nonunion: A Systematic Review

Abstract: Background The free medial femoral condyle (MFC) bone flap is an attractive option for reconstruction of scaphoid nonunion utilizing vascularized bone to augment bony healing, especially in cases of failed prior treatment or osteonecrosis. This review aims to determine the role and reliability of the free MFC flap for treatment of scaphoid nonunion. Methods A search of electronic databases was performed according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
1
6
1
Order By: Relevance
“…In this study, the corticoperiosteal flap has been demonstrated to be an effective and safe procedure for the treatment of the recalcitrant atrophic nonunion of long bones, demonstrating a rate of bone healing of 94.92% (56/59 patients) with a mean radiographic bone healing time of 4.08 AE 1.29 months (range: 2-6 months) and low morbidity of the donor site, as widely described in the literature. [4][5][6][22][23][24][25] This study has some limitations: this is a retrospective study, the site of nonunion and the hardware used to do the fixation were not homogeneous, the surgical procedure was executed by two different surgeons in two different institutions, and a relatively small number of patients were enrolled for the study. To reduce the differences caused by the execution of the surgery by two different surgeons and in two different hospitals, the inclusion and exclusion criteria had been well established and shared by the two institutions participating in the study, providing the same approach to the pathology and the same surgical technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the corticoperiosteal flap has been demonstrated to be an effective and safe procedure for the treatment of the recalcitrant atrophic nonunion of long bones, demonstrating a rate of bone healing of 94.92% (56/59 patients) with a mean radiographic bone healing time of 4.08 AE 1.29 months (range: 2-6 months) and low morbidity of the donor site, as widely described in the literature. [4][5][6][22][23][24][25] This study has some limitations: this is a retrospective study, the site of nonunion and the hardware used to do the fixation were not homogeneous, the surgical procedure was executed by two different surgeons in two different institutions, and a relatively small number of patients were enrolled for the study. To reduce the differences caused by the execution of the surgery by two different surgeons and in two different hospitals, the inclusion and exclusion criteria had been well established and shared by the two institutions participating in the study, providing the same approach to the pathology and the same surgical technique.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the corticoperiosteal flap has been demonstrated to be an effective and safe procedure for the treatment of the recalcitrant atrophic nonunion of long bones, demonstrating a rate of bone healing of 94.92% (56/59 patients) with a mean radiographic bone healing time of 4.08 ± 1.29 months (range: 2–6 months) and low morbidity of the donor site, as widely described in the literature. 4 5 6 22 23 24 25…”
Section: Discussionmentioning
confidence: 99%
“…The most widely used FVBG is the medial femoral condyle graft (MFCG) based on the descending genicular artery, which was first reported by Doi et al (2000). A meta-analysis conducted in 2021 showed an average healing rate of 93.4% (Zhou et al, 2022). In addition to providing bone, the MFCG can also carry some cartilage for the reconstruction of scaphoid nonunion associated with proximal fractures and articular cartilage damage (Kälicke et al, 2008).…”
Section: Case2mentioning
confidence: 99%
“…It offers the versatility of a small flap composed of a selection of periosteum, cortical, or cancellous bone while having potentially less donor site morbidity than traditional bone flaps. While there is mounting literature for the use of MFC flap in scaphoid nonunion, 17 its use for clavicle reconstruction is limited to case reports and small series. Clavicle nonunion is a different entity, with distinctions with regard to defects, soft tissue envelope, fixation techniques, and pathophysiological contributors to nonunion (e.g., infection, open injury, and radiotherapy), which are less often implicated in scaphoid nonunion.…”
Section: Introductionmentioning
confidence: 99%